2018
DOI: 10.3389/fimmu.2018.00686
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive NKG2C+CD57+ Natural Killer Cell and Tim-3 Expression During Viral Infections

Abstract: Repetitive stimulation by persistent pathogens such as human cytomegalovirus (HCMV) or human immunodeficiency virus (HIV) induces the differentiation of natural killer (NK) cells. This maturation pathway is characterized by the acquisition of phenotypic markers, CD2, CD57, and NKG2C, and effector functions—a process regulated by Tim-3 and orchestrated by a complex network of transcriptional factors, involving T-bet, Eomes, Zeb2, promyelocytic leukemia zinc finger protein, and Foxo3. Here, we show that persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 78 publications
2
31
2
Order By: Relevance
“…1E). This role of HIV in driving inflammation and CD4 depletion is supported by a reversal in the levels of systemic inflammation markers (Galectin-9, sCD163) and CD4 T-cell counts (and subsets) 29 after HAART ( Fig. 2e; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 80%
“…1E). This role of HIV in driving inflammation and CD4 depletion is supported by a reversal in the levels of systemic inflammation markers (Galectin-9, sCD163) and CD4 T-cell counts (and subsets) 29 after HAART ( Fig. 2e; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 80%
“…used Wanderlust was to track development of immature CD56 bright NK cells in individuals infected with HCMV using CyTOF measurements. The study found NK cells from HCMV‐infected individuals showed an early loss of CD62L accompanied with an up‐regulation of NKG2C, CD57, CD85j, and Tim‐3 …”
Section: Characterization Visualization and Interpretation Of High‐mentioning
confidence: 95%
“…The developmental trajectory is determined by finding the shortest path that connects the precursor cell to the end‐state. Kared et al . used Wanderlust was to track development of immature CD56 bright NK cells in individuals infected with HCMV using CyTOF measurements.…”
Section: Characterization Visualization and Interpretation Of High‐mentioning
confidence: 99%
See 2 more Smart Citations